Financial and Economic Aspects of St. Petersburg Paradox (Journal of Informatics and Mathematical Sciences, 2011)
This paper reviews some aspects of the history and the economic application of the St. Petersburg paradox. In the early 1700s Nicolaus and Daniel Bernoulli formulated a problem in the theory of games of chance, now known as the St. Petersburg paradox. The mathematically correct infinity entrance fee for the game is not acceptable for a real person. Examining the paradox we can see, that there are many-many interesting, economic aspects of it. Some catastrophic financial situations could have been avoided using the analysis and application of the St. Petersburg paradox. In this work I show some generalizations and applications of the paradox mainly in the field of finance and economics. The studying of the paradox and the applications of it is very useful in the teaching of probability and statistics in any college of economics. If we see the scientific aspect, we can say that there are many possibilities, unresolved issues for the financial researchers, mathematicians in the field of St. Petersburg game.
Keywords: St. Petersburg paradox; Utility; Stock exchange; portfolio